Direct measurement of the thermoelectric properties of electrochemically deposited Bi2Te3 thin films - Jose Recatala-Gomez (8373324) (2020)
The best known thermoelectric material for near room temperature heat-to-electricity conversion is bismuth telluride. Amongst the possible fabrication techniques, electrodeposition has attracted attention due to its simplicity and low cost. However, the measurement of the thermoelectric properties of electrodeposited films is challenging because of the conducting seed layer underneath the film. Here, we develop a method to directly measure the thermoelectric properties of electrodeposited bismuth telluride thin films, grown on indium tin oxide. Using this technique, the temperature dependent thermoelectric properties (Seebeck coefficient and electrical conductivity) of electrodeposited thin films have been measured down to 100 K. A parallel resistor model is employed to discern the signal of the film from the signal of the seed layer and the data are carefully analysed and contextualized with literature. Our analysis demonstrates that the thermoelectric properties of electrodeposited films can be accurately evaluated without inflicting any damage to the films. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-020-74887-z